Discovery of Two Polymorphs of TiP4N8 Synthesized from Binary Nitrides. Issue 19 (28th February 2022) - Eisenburger, Lucien; Weippert, Valentin; Paulmann, Carsten; Johrendt, Dirk; Oeckler, Oliver; Schnick, Wolfgang
Abstract: TiP4 N8 was obtained from the binary nitrides TiN and P3 N5 upon addition of NH4 F as a mineralizer at 8 GPa and 1400 °C. An intricate interplay of disorder and polymorphism was elucidated by in situ temperature‐dependent single‐crystal X‐ray diffraction, STEM‐HAADF, and the investigation of annealed samples. This revealed two polymorphs, which consist of dense networks of PN4 tetrahedra (degree of condensation κ =0.5) and either augmented triangular TiN7 prisms or triangular TiN6 prisms for α‐ and β‐TiP4 N8, respectively. The structures of TiP4 N8 exhibit body‐centered tetragonal (bct) framework topology. DFT calculations confirm the measured band gaps of α‐ and β‐TiP4 N8 (1.6–1.8 eV) and predict the thermochemistry of the polymorphs in agreement with the experiments. Abstract : The ternary Ti IV nitridophosphate TiP4 N8 has been prepared under high‐pressure high‐temperature conditions and subsequent annealing in silica ampoules. DFT calculations confirm the measured band gaps and predict the thermochemistry of two polymorphs. The synthesis of TiP4 N8 shows a promising route to new ternary nitrides with semiconducting properties.